3D Printing of Largescale Functional Nanofilm using Electrically assisted Direct Ink Deposition. (September 2022) - Zhu, Yizhen; Gogoi, Banashree; Alluri, Pranith; Suhas Despande, Mitesh; Hutchins, John; Tagbor, Edem; Alford, Terry L.; Li, Xiangjia
Abstract: Functional nanofilms show significant importance for various applications in different fields, such as sustainable energy, biomedicine, electronics, and optics. However, there are still many challenges in the fabrication of nanostructured films with tailored properties using traditional manufacturing technologies. A novel 3D printing approach called electrical field-assisted direct ink deposition (EF-DID) was developed to produce large-scale nanofilms with controllable nanostructures and patternable features. In the proposed method, the formation of nanodroplets in the direct ink deposition was investigated under an electrostatic field with high voltage. Critical printing parameters, including solution concentration, deposition height, applied voltage, and ink flow rate, were studied systematically to understand fundamental mechanisms of the nanostructures generation during the printing. In addition, the scientific relationship between deposition parameters and nanofilm properties, including film thickness, electrical conductivity, and contact angle, were explored. Finally, patterned nanofilms with well-organized nanostructures were fabricated to demonstrate potential application prospects in the field of nanotechnology.